Unvelling The Reality of The 1948 Palestinian Nakba in “Farha”: An Analysis of Framing - Maghfira Hatmaranti Rahmani Raharto; Windra Irawan (Prodi Ilmu Komunikasi UTM, 2025)
“Farha” is a Jordanian film directed by Darin J. Sallam, set against the backdrop of the 1948 Nakba in Palestine. Following its premiere in September 2021 at the Toronto International Film Festival and its release on Netflix in 2022, “Farha” was banned from screening in Israel as it was deemed to create a false narrative regarding what occurred in Palestine in 1948. Against this backdrop, this study seeks to examine how the Nakba is portrayed in the film “Farha” and whether this portrayal contains an agenda against Israel. The author obtained qualitative data through film observation and documentation, and analysed this data using Gamson and Modigliani’s framing model. The results of the analysis indicate that the framing of the Nakba in “Farha” portrays a tragedy of relatively small scale when considered within the historical context and the actual extent of the violence that occurred during the event. Furthermore, the director does not devote much attention to the political elements underlying the Nakba. However, it is evident from the narrative that the director frames the film from the perspective of Palestinians as the primary.